EFEKTIFITAS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KARANTINA OLEH PENYIDIK PEGAWAI NEGERI SIPIL - Setyawan Pramularsih; Nam Rumkel; Irham Rosyidin (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
In the community there are still many violations of the Fish and Plant Animal Quarantine Law. As a result of not meeting the requirements or procedures mentioned above, it will cause the entry of dangerous diseases in animals and plants, destroy the potential availability of animals and plants and cause disease outbreaks in Indonesia. It is even worse if the disease is zoonotic in nature, so it is disturbing for the community. One of the many cases of importation of agricultural commodities that do not meet the requirements and quarantine procedures is due to the ineffective function of Civil Servant Investigators in law enforcement in the Class II Ternate Agricultural Quarantine Center. The factors that cause law enforcement against quarantine crime in the Class II Ternate Agricultural Quarantine Center are less effective due to low public awareness and lack of coordination of related agencies. As for the less effective Law Enforcement Against Quarantine Crime, among others, is due to the lack of Apparatus Resources, namely the lack of Civil Servant Investigators at the Class II Ternate Agricultural Quarantine Center and the lack of operational budgets related to investigations.